Strategi Terbuka Al Haris Terkait HT Sebagai Komunikasi Pemilu Dengan Bupati-Wali Kota - Anasya Maulikha Rahma; Fransiska Arta Sihotang; Mirna Amelia Dewi; Noerma Kurnia Fajarwati (STIKes Ibnu Sina Ajibarang, 2024)
This research analyzes the open strategy implemented by Al Haris regarding social media (HT) in the context of political communication in the Regional Elections (Pemilu) with the Mayor. The focus is on how Al Haris utilizes social media, especially HT, to strengthen his political campaign in facing the Regional Elections. The main objective of this research is to understand how Al Haris’s use of HT affects his political communication and how it impacts public support and perceptions of him as a candidate. Qualitative methods are used in this research, involving the analysis of HT content posted by Al Haris and public responses and interactions towards it. The data used include HT posts, comments, and reactions from the public, as well as opinion surveys conducted regarding perceptions of Al Haris. The conclusion of this research highlights that Al Haris’s use of HT plays a role in building his political image, expanding the reach of his political messages, and increasing interaction with voters.